An archaeology of French scenography: staging the excavation of a collective imagination. Issue 4 (1st October 2020) - Santo, Carolina E.
ABSTRACT: This article reports and reflects on the artistic research process of Excavating the Remains of French Scenography in Prague presented at the site-specific performance festival for the Prague Quadrennial 2019. Conceived as a practice-based research, the project aimed to examine the emotional state of French scenography in relation to the Prague Quadrennial, especially due to the absence of its official national representation in 1995, and since 2003. The article reviews some of the most significant elements, moments and artistic practices that have emerged from this site-specific performance. We begin by recounting the circumstances in which the project was created for PQ19 and go on to explain what motivated Carolina E. Santo and Emmanuelle Gangloff to assemble a historical archive that became one of the project's key elements. We will then explain the project's design to invite guest-artists to perform archaeology every day for 10 days. Examining the project's core concept – intermingling archaeology and scenography – will shed light on questions such as performing the archive, participatory performance and site-specific dramaturgy, while emphasizing the relationship between artistic practice and academic research. Finally, we will show how this project became an observatory of French contemporary scenography and a celebration of its heterogeneity.